Unbearable weight: Feminism, western culture, and the body - Bordo, Susan (University of California Press, 2003)
Susan Bordo untangles the myths, ideologies, and pathologies of the modern female body. Bordo explores our tortured fascination with food, hunger, desire, and control, and its effects on women's lives
Keywords: 2000 à aujourd'hui; 2000-2009; corps; cours; discipline; fem1000; image corporelle; occident; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; études culturelles